الربط السببي اللفظي بين الجمل القرآنية بأدوات الشرط الجازمة (دراسةً دلاليةً): Causal Conjunction with Assertive Conditional letters among the Verses of Holy Qur`an (A Semantic Study) - Mumtaz, Dr. Haseeba; Shah, Dr. Syed Syar Ali (Al-Irfan, 2024)
The combination between words and meaning is very sensational for creation a fruitful discussion. The holy Qur`an, indeed it is a miracle divine book of Allah. It has thousands verses which have been somehow stretched and joined with each other. This article is concerned with studying the causal connection between the Qur’anic sentences, which we find linking to each other. They are linked, sometimes with alphabets and letters of the assertive and non-jussive condition. As we see this linking without letters, but rather it is insinuated in the mind and its meaning is taken thoughtfully. We also find the link between them due to the uniqueness of the cause (السبب) and the effect (المسبب) of the cause. And sometimes with a single cause and multiple effects, and as we find in the many proverbs in the Holy Qur’an, with multiple causes and a single effect.